Coupling between diffusion of biodiesel and large deformation in elastomers: from experimental investigation to constitutive modeling / Ch'ng Shiau Ying - Ch'ng, Shiau Ying (2014)
Due to the concern of limited fossil fuel reserve and stringent emission regulations, there is a tremendous increase in the demand for renewable energy in Malaysia. The introduction of biodiesel is by far considered as the most promising solution. Nevertheless, particular composition of biodiesel leads to material compatibility issue especially in industrial applications involving elastomeric materials. Indeed, it is established that the exposure of elastomers to biodiesel yields to a material degradation which reduces their performance. When elastomeric components are subjected to fluctuating mechanical loading and simultaneously are exposed to aggressive solvent such as biodiesel, two important aspects may contribute to the material degradations: diffusion of solvents resulting to swelling and fluctuating mechanical loading leading to fatigue failure. Since the interactions between the above aspects are not fully understood, it is crucial to investigate and to model the corresponding coupled diffusion-mechanical deformation phenomenon for durability analysis of the components. The first part of this thesis focuses on the experimental investigation on the swelling of elastomers in biodiesel in the absence and in the presence of static mechanical deformations. The former and the latter are referred to as free swelling and constrained swelling respectively. To this end, original devices and specimens are developed so that swelling tests can be conducted on the elastomers while they are simultaneously subjected to various deformation modes: simple extension, simple torsion and simultaneous extension/torsion. It is observed that the presence of static mechanical loading affects significantly the swelling characteristics of elastomers in biodiesel. Moreover, it is found that when a swollen elastomer is subjected to cyclic loading conditions, inelastic responses such stress-softening due to Mullins effect, hysteresis and permanent set decrease as the degree of swelling increases. The second part of this thesis deals with the continuum mechanical modeling of swelling. First, the theiii oretical framework of the model consistent with the second law of thermodynamics is established. More precisely, the proposed model is based on the multiplicative decomposition of the deformation gradient tensor along with the concept of strain amplification factor to account for the effect of carbon black filler. Using this theoretical framework, two particular cases are considered: (1) modeling the Mullins effect in swollen elastomers and (2) prediction of the equilibrium swelling of elastomers in biodiesel in the absence and in the presence of static mechanical deformation. It is observed that the model gives a qualitatively good agreement with experimental observations. Finally, the model for predicting the equilibrium swelling is implemented as a user-supplied subroutine in the finite element package ABAQUS to analyze the complex phenomena which occur during coupled biodiesel diffusion-mechanical deformations in elastomers.